2020
DOI: 10.1039/c9ew00882a
|View full text |Cite
|
Sign up to set email alerts
|

Balancing water quality and flows in combined sewer systems using real-time control

Abstract: An open-source control algorithm for combined sewers demonstrates how treatment plant benefits can be balanced with operation of the collection system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…Key: +, storm water and untreated wastewater were combined and released directly into river; *, storm water and treated wastewater were combined and released into environment (reproduced from Munro et al 2019) researchers have developed predictive models to minimise CSO discharges (Zhao et al 2019;Snodgrass et al 2018;Rathnayake and Faisal Anwar 2019). Troutman et al (2020) proposed a load-balancing algorithm to control storage assets within the catchment to improve flow dynamics at the WTP. This is facilitated with the use of wireless technologies and autonomous control of gates, valves and pumps within the sewer network.…”
Section: Mitigation and Treatment Strategies For Emerging Contaminants In Combined Sewer Overflowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Key: +, storm water and untreated wastewater were combined and released directly into river; *, storm water and treated wastewater were combined and released into environment (reproduced from Munro et al 2019) researchers have developed predictive models to minimise CSO discharges (Zhao et al 2019;Snodgrass et al 2018;Rathnayake and Faisal Anwar 2019). Troutman et al (2020) proposed a load-balancing algorithm to control storage assets within the catchment to improve flow dynamics at the WTP. This is facilitated with the use of wireless technologies and autonomous control of gates, valves and pumps within the sewer network.…”
Section: Mitigation and Treatment Strategies For Emerging Contaminants In Combined Sewer Overflowsmentioning
confidence: 99%
“…Several researchers have developed predictive models to minimise CSO discharges (Zhao et al 2019 ; Snodgrass et al 2018 ; Rathnayake and Faisal Anwar 2019 ). Troutman et al ( 2020 ) proposed a load-balancing algorithm to control storage assets within the catchment to improve flow dynamics at the WTP. This is facilitated with the use of wireless technologies and autonomous control of gates, valves and pumps within the sewer network.…”
Section: Mitigation and Treatment Strategies For Emerging Contaminants In Combined Sewer Overflowsmentioning
confidence: 99%
“…Strategic retention of stormwater helps to reduce contaminant loads by enhancing sedimentation and reducing downstream erosion (Kerkez et al., 2016). Real‐time control of sewer systems may also improve the treatment capacity of receiving wastewater treatment plants by removing suspended solids and limiting inflows to sustainable levels (Troutman et al., 2020). While real‐time control promises to help reverse the impacts of urbanization on river health, effective control is predicated on an accurate understanding of system states.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of water, sanitation and wastewater infrastructure is a major sustainability issue 105 . It is increasingly acknowledged that RAS could play a pivotal role in how these systems are monitored and managed 106 , including improving drinking water 107 , addressing water quality issues associated with sewerage systems 108 and monitoring and managing diverse aspects of stormwater predictions and flows 109 . Participants therefore concluded that automated monitoring and management of water infrastructure could lead to a reduction in pollution incidents, improve water quality and reduce flooding 110,111 .…”
Section: Water and Floodingmentioning
confidence: 99%